2010
DOI: 10.1242/dev.040782
|View full text |Cite
|
Sign up to set email alerts
|

Tgif1 and Tgif2 regulate Nodal signaling and are required for gastrulation

Abstract: SUMMARYTgif1 and Tgif2 are transcriptional co-repressors that limit the response to TGFb signaling and play a role in regulating retinoic-acidmediated gene expression. Mutations in human TGIF1 are associated with holoprosencephaly, but it is unclear whether this is a result of deregulation of TGFb/Nodal signaling, or of effects on other pathways. Surprisingly, mutation of Tgif1 in mice results in only relatively mild developmental phenotypes in most strain backgrounds. Here, we show that loss-of-function mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
91
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 46 publications
4
91
0
Order By: Relevance
“…One of the reasons for this might be gene redundancy. It has previously been hypothesized that the closely related homeobox gene Tgif2 might compensate for the reduced activity of Tgif1 in certain tissues or developmental contexts, since it shares many of the functional attributes of Tgif1 (12). In addition, Tgif1 and Tgif2 clearly perform overlapping functions during early embryonic development in mice (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons for this might be gene redundancy. It has previously been hypothesized that the closely related homeobox gene Tgif2 might compensate for the reduced activity of Tgif1 in certain tissues or developmental contexts, since it shares many of the functional attributes of Tgif1 (12). In addition, Tgif1 and Tgif2 clearly perform overlapping functions during early embryonic development in mice (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these mutations would cause a loss of protein function and are hypothesized to alter signaling by TGF-␤-related ligands (9)(10)(11). In mice, loss of both Tgif1 and Tgif2 is lethal, but epiblast-specific deletion of Tgif1 in combination with a null mutation in Tgif2 results in HPE, which is at least partly due to deregulation of Nodal signaling, suggesting that human TGIF1 mutations may cause HPE by affecting TGF-␤ signaling (12,13).…”
mentioning
confidence: 99%
“…It mediated transcriptional repression by recruiting HDACs and inhibiting the ability of activated SMAD2 to bind p300. The idea that TGIF had a role in limiting NODAL responses was strengthened when it was shown that mice lacking Tgif1 and Tgif2 fail in gastrulation, a defect that can be partially rescued by reducing levels of NODAL (Powers et al 2010). Moreover, conditional deletion of Tgif1/2 results in defects in left -right asymmetry, which were also alleviated by reducing the dose of NODAL (Powers et al 2010).…”
Section: Corepressorsmentioning
confidence: 99%
“…The idea that TGIF had a role in limiting NODAL responses was strengthened when it was shown that mice lacking Tgif1 and Tgif2 fail in gastrulation, a defect that can be partially rescued by reducing levels of NODAL (Powers et al 2010). Moreover, conditional deletion of Tgif1/2 results in defects in left -right asymmetry, which were also alleviated by reducing the dose of NODAL (Powers et al 2010). Other examples of corepressors that function with the SMADs are Evi-1, which cooperates with carboxy-terminal-binding protein (CtBP) to repress TGF-b, BMP, and activin-induced transcription (Izutsu et al 2001;Alliston et al 2005), and ZNF451, which blocks the ability of SMAD3/4 to recruit p300 in response to TGF-b (Feng et al 2014).…”
Section: Corepressorsmentioning
confidence: 99%
“…Tgif2 is a member of the three-amino-acid loop super family, and the TGIF2 protein encoded by Tgif2 mRNA may bind to Smad to inhibit the transforming growth factor-β signaling pathway (32). Additionally, members of the TGIF family have been documented to promote cell proliferation and differentiation and inhibit cell apoptosis (33). However, there is no reports in the role of TGIF in hypertension.…”
Section: Discussionmentioning
confidence: 99%